2017
DOI: 10.1371/journal.pone.0172994
|View full text |Cite
|
Sign up to set email alerts
|

Manchette-acrosome disorders during spermiogenesis and low efficiency of seminiferous tubules in hypercholesterolemic rabbit model

Abstract: Hypercholesterolemia is a marker for several adult chronic diseases. Recently we demonstrated that sub/infertility is also associated to Hypercholesterolemia in rabbits. Seminal alterations included: abnormal sperm morphology, decreased sperm number and declined percentage of motile sperm, among others. In this work, our objective was to evaluate the effects of hypercholesterolemia on testicular efficiency and spermiogenesis, as the latter are directly related to sperm number and morphology respectively. Tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…It has been shown that administration of tamoxifen, used in the treatment of idiopathic male infertility to HFD rabbits partially restored sperm motility, but further decreased morphology and increased spontaneous acrosome reaction ( 136 ). It has also been shown that hyper-cholesterolemic rabbits present lower testicular efficiency related to both a decrease in spermatogonial cells and an increase in germ cell apoptosis ( 137 ). On the other hand, spermiogenesis, which is the last step of spermatogenesis, was also affected in these animals.…”
Section: The Testis Cholesterol Homeostasismentioning
confidence: 99%
“…It has been shown that administration of tamoxifen, used in the treatment of idiopathic male infertility to HFD rabbits partially restored sperm motility, but further decreased morphology and increased spontaneous acrosome reaction ( 136 ). It has also been shown that hyper-cholesterolemic rabbits present lower testicular efficiency related to both a decrease in spermatogonial cells and an increase in germ cell apoptosis ( 137 ). On the other hand, spermiogenesis, which is the last step of spermatogenesis, was also affected in these animals.…”
Section: The Testis Cholesterol Homeostasismentioning
confidence: 99%
“…Metabolic abnormalities of the circulatory system have been reported to have significant adverse effects on reproductive development. Hypercholesterolemia directly affects fertilization by inducing germ cell apoptosis, worsening Leydig and Sertoli cell secretory functions, reducing sperm production and increasing sperm morphological abnormalities in rabbits [22][23][24] . Hypercholesterolemia and hyperlipidemia during pregnancy inhibited blastocyst development and altered oocyte metabolism, leading to defects in fetal glucose supply and affecting fetal vascular development [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we reported the localization of actin, tubulin and ganglioside GM1 in the elongation area [ 20 ]. This particular localization could indicate that microtubules interact with a network of actin filaments that may be associated with membrane microdomains in the elongation area.…”
Section: Introductionmentioning
confidence: 99%
“…Testicles generate less number of ejaculated sperm cells during spermatogenesis under high-fat diet but the sperm number is recovered when olive oil is added to diet [ 6 ]. The sperm number reduction is associated with a testicular efficiency decline in hypercholesterolemic rabbits[ 20 ]. However, testicular efficiency under the administration of olive oil remains unknown until now.…”
Section: Introductionmentioning
confidence: 99%